HTML, XHTML & CSS for dummies - Tittel, Ed; Noble, Jeff (For dummies, 2011)
You don?t have to be an expert programmer to build great Web pages. This book will not only show you the design and technical elements you need to create good-looking, readable Web pages-- it will give you the confidence to get started!